2012
DOI: 10.3109/00365548.2011.645504
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens in the lower respiratory tract of intensive care unit patients: Impact of duration of hospital care and mechanical ventilation

Abstract: The occurrence of pathogens with high antibiotic resistance in the lower respiratory tract increases with increased duration of hospital care and mechanical ventilation. An equally important result is that pathogens resistant to third-generation cephalosporins were more common than expected, even after a very short duration of hospital care and mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 99 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…Our models also allowed for quantification in that we could depict the amount of increase in resistance. This goes beyond existing analyses from comparable studies with smaller numbers [11,18].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our models also allowed for quantification in that we could depict the amount of increase in resistance. This goes beyond existing analyses from comparable studies with smaller numbers [11,18].…”
Section: Discussionmentioning
confidence: 76%
“…Decreasing antibiotic susceptibility with increasing length of hospital stay has been shown for the colonization or infection of certain organ systems [17]. Two studies with modest numbers of isolates (n ¼ 321 to n ¼ 443) have scrutinized this question for the respiratory tract: while a single-centre study found a rise in bacterial resistance to cefotaxime in the lower respiratory tract with increasing length of stay, a multicentre study on ventilatorassociated pneumonia failed to do so, mainly due to large-scale variation across the four treatment centres [11,18].…”
Section: Introductionmentioning
confidence: 99%
“…Low awareness of infection prevention and high transmission between patients and the community is challenging in LMICs. The prevalence of GNB is lower in some regions especially in Europe, the US, and Canada except in the context of hospital-acquired pneumonia;4951 notably different from reports from Asian countries, as reflected by recommendations made by the ATS and BTS in their respective guidelines 3,5,47…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, patients with bacterial infections tended to have a more severe course according to PICU admission rates, respiratory support necessity, clinical disease severity scales and length of hospitalization [ 8 ]. Previous research shows that the occurrence of pathogens with high antibiotic resistance in the lower respiratory tract increases with increased duration of hospital care and mechanical ventilation [ 9 ]. Alternatively, knowledge of a reduced duration of ventilation can be used to justify a prospective trial to assess the proper employment of antibiotics in children with severe CAP requiring invasive ventilation [ 10 ].…”
mentioning
confidence: 99%